2014
DOI: 10.1111/ejh.12409
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the pregnane X and retinoid receptors PXR, RAR and RXR may regulate transcription of the transporter hOCT1 in chronic myeloid leukaemia cells

Abstract: The expression and activity of the uptake transporter human organic cation transporter 1 (hOCT1; SLC22A1) is an independent predictor of response to imatinib treatment in patients with chronic myeloid leukaemia (CML). We have recently shown that peroxisome proliferator-activated receptor (PPAR) activation can increase the killing effect of imatinib in CML cells, due to upregulated hOCT1 gene expression and increased imatinib uptake. To investigate the role of activation of nuclear receptors other than PPAR in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Therefore, the authors hypothesize that rifampicin induces OCT1 in hepatocytes, which subsequently increases the uptake of metformin into hepatocytes, resulting in the increased effect of metformin (Cho et al, 2011). Similarly, agonists of PXR induced OCT1 mRNA in the chronic myeloid leukaemia (CML) cell line and primary CML cells (Austin et al, 2015). However, contradictory data have been also published indicating the downregulation of OCT1 mRNA in human hepatocytes after treatment with rifampicin Badolo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors hypothesize that rifampicin induces OCT1 in hepatocytes, which subsequently increases the uptake of metformin into hepatocytes, resulting in the increased effect of metformin (Cho et al, 2011). Similarly, agonists of PXR induced OCT1 mRNA in the chronic myeloid leukaemia (CML) cell line and primary CML cells (Austin et al, 2015). However, contradictory data have been also published indicating the downregulation of OCT1 mRNA in human hepatocytes after treatment with rifampicin Badolo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was demonstrated that PXR-null mice developed B cell lymphoma in an age-dependent manner, suggesting a tumor suppressor role for PXR in B-1 cells (Casey et al, 2011). In chronic myeloid leukemia (CML) patients, it is known that the expression and activity of the uptake transporter human organic cation transporter 1 (hOCT1) positively determines the favorable outcome to Imatinib treatment (Austin et al, 2015). Pharmacologic activation of PXR with rifampicin or SR12813 in KCL22 CML cell line and CML primary cells resulted in up-regulation of hOCT1 expression, suggesting that PXR agonists may be potentially used to improve the efficacy of Imatinib in patients with CML (Austin et al, 2015).…”
Section: Differential Role Of Pxr In Cancermentioning
confidence: 99%
“…In chronic myeloid leukemia (CML) patients, it is known that the expression and activity of the uptake transporter human organic cation transporter 1 (hOCT1) positively determines the favorable outcome to Imatinib treatment (Austin et al, 2015). Pharmacologic activation of PXR with rifampicin or SR12813 in KCL22 CML cell line and CML primary cells resulted in up-regulation of hOCT1 expression, suggesting that PXR agonists may be potentially used to improve the efficacy of Imatinib in patients with CML (Austin et al, 2015). In another study of multiple myeloma, gene expression of uptake carriers, xenobiotic receptors, phase I and II drug metabolizing enzymes, and efflux transporters was examined in multiple myeloma cells of newly-diagnosed patients (Hassen et al, 2014).…”
Section: Differential Role Of Pxr In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was hypothesized that rifampicin may induce OCT1 in hepatocytes and thus increase the uptake of metformin into hepatocytes (Cho et al, 2011). In other studies, agonists of PXR have been found to mildly induce OCT1 mRNA in the chronic myeloid leukemia (CML) cell line KCL22 and primary CML cells (Austin et al, 2015). Rat Slc22a1 gen has been clearly demonstrated as a target of rat Pxr and pregnenolone16a-carbonitrile (PCN), a prototype rodent Pxr ligand, significantly induced Oct1 in the rat liver (Maeda et al, 2007).…”
Section: Ligand-dependent Nuclear Receptor-mediated Regulationmentioning
confidence: 99%